Integration of molecular profiles in a longitudinal wellness profiling cohort - Abdellah Tebani (Nature Portfolio, 2020)
An important aspect of precision medicine is to probe the stability in molecular profiles among healthy individuals over time. Here, the authors sample a longitudinal wellness cohort and analyse blood molecular profiles as well as gut microbiota composition.